Buddhism: Introducing the Buddhist Experience. Donald W. Mitchell. - Chryssides, George D. (Buddhist Studies Review, 2003)
Buddhism: Introducing the Buddhist Experience. Donald W. Mitchell. Oxford University Press, New York 2002. xvi, 368 pp. £16.99 ISBN 0 19 513952 6.